Analisis Melodi Dan Syair Pada Buku Ende. No. 512. “Didalani Jesus Tano Dohot Laut” Di HKBP Sisordak Resort Simamora - Lasmaria Purba; Diana Situmeang; Testi Bazarni Zebua (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2023)
The aim of this research is to analyze the melody of the song and analyze the lyrics of the song Buku Ende Number 512. "Di Dalani Jesus Tano Dohot Laut" which includes motifs, phrases, melodies, scales, ambitus, melodic contours, harmony, rhythm, tempo, texture, language style, rhyme patterns, and meter patterns. This song is sung according to the church liturgy. This research uses qualitative research methods with research instruments of observation, interviews, literature and documentation. This research was carried out by collecting information through field research to obtain results that were processed to be certain. The results of this research reveal that the song Buku Ende Number 512. "Di Dalani Jesus Tano Dohot Laut" has a 2/4 time signature with a tempo of MM 90 moderate, with a basic tone of Es=DO, consisting of 34 bars. With the rhyme pattern a a a a, this song has a meter pattern of 12,12,12,11,12 which is called the long meter meter pattern. In terms of poetry, this song has 2 phrases, and 3 motifs (a, b, c, d) moving chords from I, V, IV.